ANLISIS TANAMAN PUTRI MALU SEBAGAI SARANA PEMAHAMAN KONSEP DSAR TUMBUHAN PEKA TERHADAP RANGSANGAN - Septia Shylviana; Rapida Idami; Nurul Hasana (JOURNAL SAINS STUDENT RESEARCH, 2025)
putrimalu or what is known by its scientific name Mimosa pudica, is a plant that has extraordinary sensitive properties. Each part of this plant shows different levels of sensitivity to stimuli, making it an interesting object to study. The blushing plant has a unique mechanism called turgor pressure, which plays an important role in the plant's reaction to touch. When air levels in plant cells decrease, reactions to stimuli become more visible. The movements that occur in this plant are included in the category of seismonastic movement, where the direction of the plant's movement is influenced by the source of the stimulus it receives. Interestingly, the time it takes for each part of the mollusk plant to respond to stimulation varies. This is influenced by various factors, such as weather conditions, air humidity, and the softness or roughness of the stimulus provided. Thus, the mollusk is not just a plant, but is also an amazing example of the adaptation and response of plant life to its surrounding environment.